ANALISIS PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP)DALAM MENUNJANG KELANCARAN OPERASIONAL PURCHASING DI PT. SUKSES MITRA SEJAHTERA - Puspitasari, Yossy; Fauji, Diah Ayu Septi; Kurniawan, Rony (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The background of this research is to support the smooth running of Purchasing operations by using Standard Operational Procedures (SOP) as controls and work system guidelines to create an adequate internal control system. Standard Operational Procedures (SOP) are the main needs of the company in carrying out all company activities. Implementation of SOP properly can result in the smooth running of the company's operational activities. SOPs that are clear and easy to understand can help employees to be able to work by showing good performance in accordance with the wishes of the company. The type of research used in this study uses descriptive qualitative methods. Data collection techniques in this study used sources, namely interviews, observations, and document utilization. The informant in this research is the Head of Purchasing. The conclusion of this research is that the application of standard operating procedures plays an important role in the smooth running of Purchasing operations. The purpose of this study is to analyze the application of Standard Operating Procedures (SOP) in supporting smooth operations. The benefits and objectives of SOP purchasing are to regulate the flow of purchases so that they are more orderly and regular when there is an audit. Based on the results of the study, the application of SOPs in purchasing is very influential in improving company performance, because SOPs are guidelines, handbooks and procedures for doing the work of every employee in each jobdesk.